Real-world Effectiveness of Elagolix When Used in Combination With Hormonal Contraceptives [A79]. (May 2022) - Levy, Barbara; Fairbrothers, David L.; McKenna, Kelsey; Westhoff, Carolyn; Cross, Sarah; Frakes, Eli
Abstract : INTRODUCTION: Real-world data on the use of elagolix, an oral gonadotropin-releasing hormone (GnRH) receptor antagonist, in combination with hormonal contraceptives (HC) is limited. This analysis evaluated endometriosis-associated pain in women treated with elagolix (150 mg once daily or 200 mg twice daily) in combination with HCs in routine clinical practice. METHODS: This retrospective chart review utilized Dorsata data available via their clinical and claims data network (Athena EMR and Surescripts). The primary outcome was the change in endometriosis pain in women receiving elagolix concomitantly with HCs (progesterone only oral contraceptives [POPs], long-acting reversible contraception [LARC], or estrogen containing combined oral contraceptives [COCs]) at the first follow-up visit vs baseline (elagolix initiation). RESULTS: Women (N=193) had a mean age of 28.5 years, and most (75.1%) had received previous endometriosis-related treatment. Overall, endometriosis pain was reported as better in 79.3% (n=153) of women who received elagolix concomitantly with HCs and specifically in 72.7% of women receiving COC (n=24), 79.2% of women receiving LARC (n=76), and 80.5% of women receiving POP (n=33). Documented discontinuations included anxiety/depression (n=4), mood changes (n=2), nausea (n=1), and other (n=2) or increased (n=2) pain. This study was limited geographically and by sample size. CONCLUSION: This analysis demonstrated that women taking elagolix for endometriosis-associated pain had improvement regardless of the HC used. Future studies are needed on the safety and efficacy of concomitant use of elagolix with specific hormonal contraceptives.